Deciphering the multifaceted mechanism of Shuang Huang Lian in treating upper respiratory tract infections: A metabolomics-based network pharmacology approach - Gang Xu; Akshay Suresh Patil; Ruhan Wei; Dan Liu; Aimin Zhou; Yan Xu (Phytomedicine Plus)
Background and purpose: Shuang Huang Lian (SHL), a traditional Chinese medicine (TCM) formula consisting of extracts from Lonicerae japonicae flos, Forsythiae fructus, and Scutellariae radix, is widely recognized for its efficacy in treating upper respiratory tract infections (URTIs). Recommended by the 2011 Chinese Guidelines for Diagnosis and Treatment of Influenza, SHL's therapeutic potential has long been valued in clinical practice. However, its precise mechanisms of action against URTIs remain unclear, necessitating further exploration. Methods: This study investigates the molecular mechanisms and identifies the key active components and pivotal protein targets of SHL in URTI treatment using a network pharmacology approach. We based our analysis on pharmacologically active SHL components we previously identified through untargeted metabolomics profiling. Key cheminformatics and bioinformatics platforms and databases, including ADMETlab, SEA, PASS, Super-Pred, SwissTargetPrediction, PharmMapper, and GeneCards, were used to predict the drug-like properties of active SHL components and identify protein targets shared between the active SHL components and the URTI-related disease genes. A protein-protein interaction (PPI) network was constructed, and gene ontology (GO), KEGG, and Reactome enrichment analyses were conducted to elucidate the biological functions relevant to URTIs. Target-target interaction (TTI) network construction and modularity analysis were also performed. Finally, pivotal protein targets and key active SHL components were validated through molecular docking simulations and in vitro cell culture experiments. Results: Our analysis identified TNF, CASP1, and MAPK14 as pivotal protein targets in SHL's action against URTIs, with brusatol, an active SHL component, confirmed as a critical ligand that modulates these targets. Conclusion: This comprehensive study elucidates the multifaceted mechanisms underlying SHL's efficacy in treating URTIs, supporting its traditional use and highlighting its potential for novel therapeutic development.